From conventional drainage to sustainable stormwater management: Beyond the technical challenges. (1st August 2018) - Goulden, Shula; Portman, Michelle E.; Carmon, Naomi; Alon-Mozes, Tal
Abstract: Countries and cities are increasingly recognizing the value of adopting Sustainable Stormwater Management (SSWM) goals and measures. SSWM serves multiple hydrological, ecological, social and economic goals and can replace substantial parts of conventional drainage infrastructure. Following international experience in the socio-technical nature of transitions in stormwater management, this research investigates how socio-institutional factors enable the transition from conventional to sustainable stormwater management over time. The research is based on analysing available relevant documents, semi-structured interviews and focus groups, all in a single country case study (Israel). We found significant changes in professional awareness and discourse, some advances in professional standards of work and changes to the regulative system, supporting infiltration practices in particular. We concluded that the three-pillared socio-institutional framework, composed of cultural-cognitive, normative and regulative changes, was insightful for mapping factors supporting transition from conventional drainage to SSWM. Elements within the three pillars can work simultaneously and synergistically to achieve widespread change. At the same time, while SSWM always strives to achieve multiple goals, the order of priority of the various goals may differ from place to place and may change over time. Thus the transition process across the socio-institutional pillars should be renewed if and when the priority of goals changes. The urban and regional planning system can play a crucial role in enhancing the transition process from conventional to sustainable stormwater management. These conclusions may be relevant to other localities and countries that are struggling with such transitions to sustainability. Graphical abstract: Highlights: Sustainable Stormwater Management covers environmental, social and economic goals. Three-pillared socio-institutional factors help to map sustainability transitions. The three pillars work synergistically and simultaneously to support the transition. The urban planning system plays a key role in supporting the transition process. Changing priorities require a renewed socio-institutional transition process.